OTSM-SCMA: Code-Domain NOMA based Orthogonal Time Sequency Multiplexing Modulation - Thomas A.; Sangeeta N.; Deka K.; Sharma S.; Rajesh A. (My University, 2025)
In this paper, we present a code-domain (CD) non-orthogonal multiple access (NOMA) approach for orthogonal time sequency multiplexing (OTSM) modulation. OTSM is a recently proposed 2D modulation technique, where the data symbols are in the delay-sequency domain. Further, sparse code multiple access (SCMA) is a CD NOMA, which is more efficient than power domain NOMA techniques due to the codeword data symbols. The OTSM modulation with respect to codeword data symbols allocation is more challenging and not explored in the literature. The proposed OTSM-SCMA scheme focuses in this direction, and uses SCMA codeword symbols instead of QAM symbols. For data detection of the OTSM-SCMA scheme, we propose a two-stage sequential detection method. First stage is independent OTSM detection using Gauss-Seidal (GS) method and the second stage is SCMA detection using message-passing (MP) algorithm. The simulation results show that the proposed OTSM-SCMA scheme can achieve a notably higher rate compared to OTSM-OMA (orthogonal multiple access). Also, OTSM-SCMA gives comparable BER performance with the OTSM-OMA scheme. © 2023 IEEE.